2021
DOI: 10.1016/j.ijmmb.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae and SARS-CoV-2: Is there a role for investigation?

Abstract: During the current pandemic of COVID-19, the authors observed that during screening test for SARS-CoV-2 targeting the E-gene by qRT-PCR, few nasopharyngeal/oropharyngeal samples showed amplification signals at late cycle threshold (C T -value) > 35 despite being negative for other confirmatory target genes. Thirty such samples (taken as cases) showing detectable C T of > 35 cycle in E-gene which were negative for other target genes of SARS-CoV-2 and 30 samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Yet influenza-exposed eosinophils have been shown to stimulate CD8+ T cell activation and proliferation in vitro, indicating a potential role for eosinophils as antigen-presenting cells in influenza infection during asthma [ 88 ]. Therefore it might be suggested that the protection afforded to Th-2 phenotypes against severe outcomes is a result of prolonged eosinophilia and partial cell-mediated immunity conferred from previous infections, such as Haemophilus influenzae , common cold viruses or SARS, as proposed by Bokatory et al [ 93 ].…”
Section: Allergic-asthma and Hypoxiamentioning
confidence: 99%
“…Yet influenza-exposed eosinophils have been shown to stimulate CD8+ T cell activation and proliferation in vitro, indicating a potential role for eosinophils as antigen-presenting cells in influenza infection during asthma [ 88 ]. Therefore it might be suggested that the protection afforded to Th-2 phenotypes against severe outcomes is a result of prolonged eosinophilia and partial cell-mediated immunity conferred from previous infections, such as Haemophilus influenzae , common cold viruses or SARS, as proposed by Bokatory et al [ 93 ].…”
Section: Allergic-asthma and Hypoxiamentioning
confidence: 99%